Interaction between updated FR-CG algorithms with optimal Cuckoo algorithm - Rana Z. Alkawaz; Abbas Y. AlBayati; Marwan S. Jameel (Institute of Advanced Engineering and Science, 2020)
In this article we have derived two versions, ξk and ρk were derived from an algorithm based on the first suggested modified Fletcher-Reeves method in the article for the two-term CG method and another term to get a downward search towards the function minimum point with the search for an inaccurate line and we have proved rapprochement. These two algorithms combined with the Cuckoo algorithm to achieve a remarkable performance in reducing the number of repetitions in order to reach the minimization of 10 functions is unconstrained in the numerical results.